Investigating the inflation-output nexus for the euro area: Old questions and new results - Hans-Eggert Reimers; Dieter Gerdesmeier; Barbara Roffia (Economies, 2023)
The relationship between inflation and real GDP growth is one of the most widely researched topics in macroeconomics. At the same time, it is certainly not an exaggeration to claim that this nexus also stands at the heart of monetary policy, given the fact that low inflation in combination with high and sustained output growth should be the central objective of any sound economic policy. The latter notion becomes even more obvious when taking account of the fact that many central banks all over the world have selected target levels for inflation and communicated them to the public. Against this background, it is of utmost importance for central banks to understand more about the nature and formation of the relationship between inflation and real GDP. This study attempts to shed more light on the specific shape of this relationship for the euro area and, more specifically, on the issue of possible regime shifts therein. The analysis provides strong evidence for non-linear effects in the euro area. As a by-product, and seemingly the novel contribution, of this paper, the methods used allow for the quantification of a switching point across the different regimes. It is found that this breakpoint closely matches the ECB's previous definitions of price stability and its new inflation target of 2%. While these results look encouraging, further research in this area seems to be warranted.
Keywords: 330; monetary policy; inflation; euro area; threshold regression; smooth transition regressions